(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Allergic diseases and especially diseases of the respiratory tract are environmentally dependent diseases, since the phenotypic realization of hereditary predisposition to them is always carried out under the influence of environmental factors. That is why, for example, bronchial asthma, especially in children, is a sensitive marker of air pollution.